Cost-efficient anthropomorphic head phantom for quantitative image quality assessment in cone beam CT. (1st November 2022) - Wang, Yichao; Dankelman, Jenny; Ruijters, Danny
Abstract: In this study, a novel anthropomorphic head phantom for quantitative image quality assessment in cone beam computed tomography (CBCT) is proposed. The phantom is composed of tissue equivalent materials (TEMs) which are suitable for cost-efficient fabrication methods such as silicone casting and 3D printing. A monocalcium phosphate/gypsum mixture (MCPHG), nylon and a silyl modified polymer gel (SMP) are proposed as bone, muscle and brain equivalent materials respectively. The TEMs were evaluated for their radiodensity in terms of Hounsfield Units (HU) and their x-ray scatter characteristics. The median radiodensity and inter quartile range (IQR) of the MCPHG and SMP were found to be within the range of the theoretical radiodensity for bone and brain tissue: 922 (IQR = 156) and 47 (IQR = 7) HU respectively. The median radiodensity of nylon was slightly outside of the HU range of muscle tissue, but within the HU range of a combination of muscle and adipose tissue: −18 (IQR = 40) HU. The median ratios between the measured scatter characteristics and simulated tissues were between 0.84 and 1.13 (IQR between 0.05 and 0.14). The preliminary results of this study show that the proposed design and TEMs are potentially suitable for the fabrication of a cost-efficient anthropomorphic head phantom for quantitative image quality assessment in CT or CBCT.